Customer awareness and factors influencing Islamic banking adoption in Bintulu, Malaysia - Latip, Malisah (2015)
The emergence of Islamic banking system in the contemporary banking industry has made a huge impact on the financial industry across the world. Despite the enthusiasm to promote Islamic banking systems internationally, Malaysia has yet to achieve satisfactory level of awareness and adoption of Islamic banking from its national perspective. This research attempts 1) to examine the awareness of Islamic banking and 2) to identify the influential factors that are associated with Islamic banking adoption among the Muslims and non-Muslims population in Sarawak, Malaysia by extending the renowned framework of Diffusion of Innovation (DOI) theory with the “adoption of Islamic banking” being the dependent variable, this study comprises of seven independent variables. There are four attributes of innovation, namely; 1) relative advantage, 2) compatibility, 3) observability and 4) complexity and three additional variables, namely 5) perceived risk, 6) perceived trust and 7) customer innovativeness. The simple random sampling method is used whereby a questionnaire is administered to 436 respondents from Bintulu, Sarawak. The findings of descriptive analysis show that, the awareness of Islamic banking products and services are relatively low among the respondents, regardless of their religious backgrounds. Initially, exploratory factor analysis has generated six factor solutions. By the filtration of the logistic regression equation, three factors, namely; 1) compatibility, 2) relative advantage and observability and 3) complexity are proven to have significant influence on customers’ adoption of Islamic banking products and services in Bintulu. Thus, the study recommends that the banking industry gives serious attention on these attributes of innovation to increase the adoption level among customers. Banks need to enhance accessibility, profitability and service quality factors which are critical success factors that affect an organization’s competitiveness. In addition, banks need to reduce the complexity of transactional procedure in order to raise the acceptance of Islamic products among the public and increase its usage.